Application Of Mysur In Improving Arabic Grammar Mastery - Mohamad Hussin; Hanan Salleh; Triyo Supriyatno (Ijaz Arabi Journal of Arabic Learning, 2023)
This study aimed to evaluate the effectiveness of using the Mysūr website to improve students’ Arabic grammar skills. Previous studies have shown that students have poor grammar proficiency due to the lack of quality teaching materials and the neglect of modern technological elements in learning. Therefore, an interactive, efficient, and flexible website was developed based on multimedia technology and self-interactivity. Users can use the provided materials anytime, anywhere. Thirty-two students were selected through targeted sampling and pretesting, 10-week intervention, and post-intervention testing to assess the approach's effectiveness. The mean difference between the pretest and posttest measures the effectiveness of the developed website-based learning approach. The study results showed improved performance for each of the revealed grammatical elements. This indicates a significant relationship between the learning approaches and students’ grammatical proficiency. The study’s conclusions show that courses to learning supported by multimedia technology and meeting current needs are interactive, easily accessible, and help improve student achievement.